Strategic Approaches in Educational Administration and Management for Advancing Sustainable Development - Atthakorn , Suthinee; Kaiyanan, Chakorn; Phoorisophon , Theeraphot; Ludpa , Yuvares; Seti , Sirikanya; Lavong, Anucha; Pliankham , Pichit (Journal of Education and Learning Reviews, 2024)
Background and Aims: Educational administration and management are essential for advancing sustainable development because they shape the policies, leadership, and practices that underpin institutional sustainability initiatives. Sustainable governance and operations can foster an environmental culture and prepare students to face global challenges. This paper aims to identify, analyze, and evaluate strategic approaches for advancing sustainable development. Methodology: The methodology combines a systematic literature review with stringent data collection and analysis procedures to comprehensively examine strategic approaches in educational administration and management. The study employs a variety of data sources and analytical tools to identify effective practices, emerging trends, and gaps in the literature, providing important insights into advancing sustainable development in education. Results: The finding found that integrating sustainability into educational administration and management is critical for fostering an environmental stewardship culture and achieving long-term goals. Effective policies, transformational leadership, and active stakeholder engagement are critical to driving successful sustainability initiatives. Successful case studies, such as the Green School and UC Berkeley, demonstrate that by incorporating sustainability into the curriculum and leveraging technological innovations, educational institutions can address future challenges while increasing operational efficiency. Conclusion: Integrating sustainability into educational administration and management is critical for developing an environmental stewardship culture and meeting long-term objectives. The Green School and UC Berkeley have demonstrated how effective policies, leadership, and stakeholder engagement can improve operational efficiency and address future challenges by incorporating sustainability into curriculum and technology.